Carotol: A Sesquiterpenoid Isolated from Carrot Seed Oil - Chahal, K.K.; Kaur, P.; Kataria, D.; Kaur, R. (Asian Journal of Chemistry, 2016)
Essential oil obtained from carrot (Daucus carota) seeds by hydrodistillation was analyzed by gas chromatography-mass spectrometry (GC-MS). A total of 51 compounds, accounting for 97.8 % of the total oil were identified. Carotol, a sesquiterpenoid was found to be the major compound present in the carrot seed essential oil while the other compounds were daucol, daucene, b-cubenene, b-farnesene, etc. Carotol was isolated from carrot seed essential oil by column chromatography which was chemically transformed into daucol, carotol ether, 4-chloro carotol and carotol amide. The structures of these compounds were elucidated on the basis of FTIR, 1H NMR and 13C NMR.